Pagan races of the Malay peninsula - Skeat, Walter William (Macmillan, 1906)
vol. I. Preface. Introduction. pt. 1. Race. pt. 2. Manners and customs. Appendix. Place and personal names.--vol. II. pt. 3. Religion. pt. 4. Language. Appendix. Comparative vocabulary of aboriginal dialects. Index of subjects. Index of proper names. Index of native words.